Optimal Protocol for the Differentiation and Metabolic Analysis of Human Adipose Stromal Cells - Lee, Mi-Jeong (Methods Enzymol, 2014)
Obesity is reaching epidemic proportions so there is growing interest in the mechanisms that regulates adipose tissue development and function. Although murine adipose cell lines are useful for many mechanistic studies, primary human adipose stromal cells (ASCs), which can be isolated from distinct adipose depots and cultured in vitro, have clear translational relevance. We describe the methods to isolate, culture, and differentiate human ASCs to adipocytes that respond to physiologically relevant hormones, such as insulin and β-adrenergic agonists. We also describe methods for assaying hormonal effects on glucose transport and lipolysis.